DESKRIPSI PELAKSANAAN PEMBERANTASAN SARANG NYAMUK (PSN) DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN KARANGPUCUNG KECAMATAN PURWOKERTO SELATAN KABUPATEN BANYUMAS TAHUN 2014 - Ratna Pramurditya; Arif Widyanto (Buletin Keslingmas, 2015)
DHF incidence rate increases caused by the lack of clean and healthy behaviors. DHF is causedby dengue virus by mosquitoes of the genus Aedes (Aedes aegypti and Aedes albopictus). Thehighest number of DHF at 2013 in Banyumas regency is South of Purwokerto district (92 cases).Karangpucung village (21 cases) the highest DHF. Mosquito nest eradication action DHF includesurvey of mosquito larvae was done in Karang pucung village but the larvae-free rate (ABJ) not yet toreach the target (94.09%), so the researcher wanted to discover the implementation of mosquito nesteradication dengue hemorrhagic fever in Karang pucung village South of Purwokerto districtBanyumas regency year 2014.Type research is observation with descriptive analysis qualitative survey approach whichprovides an overview the implementation of mosquito nest eradication DHF in Karang pucung village.Sample from 98 families head in 12 RW at the Karangpucung village by Systematic RandomSampling.The implementation of mosquito nest eradication DHF in Karangpucung Village done 95 familieshead (97%). RW 1 (39%) and RW 2 (29%) the lowest implementation of mosquito nest eradication,RW 9 (66%) and RW 7 (63%) the highest implementation of mosquito nest eradication. Survey motionplus 3M low of practice was to use a mosquito net (4%), the larvae-eating fish (6%), the use of wiregauze on the ventilation holes (12%), sowing abate (17%). The survey result, larvae in Karangpucungvillage the larvae-free rate (ABJ) not eligible (79%), HI are not eligible (21%), CI does not qualify(5%), BI eligible (23%). RW 2 and 4 have the lowest ABJ and HI, CI, BI highest, in accordance withthe highest number of dengue cases in RW 4 (5 cases) and RW 2 (1 case).Researcher conclusion is the implementation of mosquito nest eradication dengue hemorrhagicfever in Karangpucung Village, not all of the people active of mosquito nest eradication denguehemorrhagic fever in the movement 3M plus. Many mosquito larvae still found so mosquito nesteradication target not reach (ABJ ≥ 95%). Community and cadres suggested more active in theimplementation of mosquito nest eradication.